Acute conduction recurrence of mitral isthmus: Incidence, clinical characteristics, and implications. Issue 12 (12th November 2020) - Lu, Xiaofeng; Peng, Shi; Xu, Juan; Wang, Rui; Pang, Lingpin; Zhou, Genqing; Wei, Yong; Cai, Lidong; Wu, Xiaoyu; Guo, Shuai; Huang, Dayang; Li, Wenhua; et al.
Abstract: Background: Data on the incidence, clinical characteristics, and implications of acute conduction recurrence during mitral isthmus (MI) ablation are scarce. Methods: MI ablation was performed in patients with atrial fibrillation. After confirming bidirectional conduction block, the acute conduction recurrence of MI was systematically evaluated. Clinical and electrophysiological characteristics were analyzed. Results: A total of 66 consecutive patients in whom bidirectional conduction block of MI was achieved were prospectively enrolled in a single center. Acute conduction recurrence of MI developed in 12 (18.2%) patients within 14.2 ± 11.5 minutes after the confirmation of bidirectional conduction block. There were two recurrent conduction breakthrough sites of MI along the course of the great cardiac vein (4.5 ± 3.5 min) in two patients and 11 along the course of the ligament of Marshall (LOM) (16.0 ± 11.6 min, P = .035) in 11 patients. LOM accounted for most (84.6%, 11/13) acute MI conduction recurrence. MI length, total ablation time, and procedure time for MI were greater in patients with acute conduction recurrence than in those without acute conduction recurrence. During follow‐up, arrhythmia recurrences were less observed in patients with acute conduction when compared to patients without acute conduction recurrence (0% vs 26.4%, P = .055). Conclusion: Acute conduction recurrence, predominantly due to recurrent LOM conduction, was a common phenomenon during MI ablation, and its evaluation should therefore be the focus to improve MI ablation efficacy and durability.